A Novel Iterative Method to the Synthesis of Subarrayed Monopulse Linear Arrays - Cui, Chao-Yi; Li, Xin; Huang, Yan; Jiao, Yong-Chang (UK, Europe, China Millimetre Waves and THZ Technology Workshop (Online), 2020)
In this paper, a novel hybrid iterative method which combines iterative Fourier technique (IFT) with the fuzzy C-means clustering algorithm (FCM) is proposed to synthesize subarrayed monopulse linear arrays. In the synthesis problems, when the sidelobe level objective is achieved, the FCM is integrated into the IFT loops to handle the subarray partition problems. Synthesis of small and large monopulse arrays with different number of subarrays are reported by comparisons with state-of-the-art literatures to demonstrate the effectiveness of the proposed method.